Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Rosidin Rosidin; Maharani Maharani; Sastawati Putri Laia; Ngatimin Ngatimin (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research endeavors to scrutinize the ramifications of Good Corporate Governance (GCG) on the financial performance of companies accredited by the Indonesia Stock Exchange (IDX). GCG functions as a pivotal framework in corporate stewardship, principally aimed at augmenting investor confidence and fostering superior financial outcomes. Employing a quantitative paradigm, this study draws upon secondary data derived from the financial statements and annual reports of IDX-listed corporations spanning the period from 2019 to 2023. The independent variables under examination encompass the proportion of independent commissioners, institutional ownership, and the functionality of the audit committee, whereas the dependent variable, financial performance, is operationalized through Return on Assets (ROA), Return on Equity (ROE), and Tobin’s Q. Empirical findings reveal a discernible and significant impact of GCG on corporate financial performance. More precisely, the proportion of independent commissioners and the efficacy of the audit committee exhibit a positive association. with ROA and ROE. Conversely, institutional ownership demonstrates a more nuanced and somewhat inconsistent relationship with the different metrics of financial performance. These insights carry substantial weight for regulatory bodies, corporate leadership, and the investment community, underscoring the imperative to reinforce robust corporate governance practices as a prerequisite for achieving sustainable financial prosperity.